The lead pollution history of Law Dome, Antarctica, from isotopic measurements on ice cores: 1500 AD to 1989 AD - Vallelonga, Paul; Van de Velde, Katja; Candelone, Jean; Morgan, V.; Boutron, C.; Rosman, Kevin (Elsevier Science BV, 2002)
Lead isotopic compositions and Pb and Ba concentrations have been measured in ice cores from Law Dome, East Antarctica, covering the past 6500 years. ‘Natural’ background concentrations of Pb (0.4 pg/g) and Ba (1.3 pg/g) are observed until 1884 AD, after which increased Pb concentrations and lowered 206Pb/207Pb ratios indicate the influence of anthropogenic Pb. The isotopic composition of ‘natural’ Pb varies within the range 206Pb/207Pb=1.20–1.25 and 208Pb/207Pb=2.46–2.50, with an average rock and soil dust Pb contribution of 8–12%. A major pollution event is observed at Law Dome between 1884 and 1908 AD, elevating the Pb concentration four-fold and changing 206Pb/207Pb ratios in the ice to 1.12. Based on Pb isotopic systematics and Pb emission statistics, this is attributed to Pb mined at Broken Hill and smelted at Broken Hill and Port Pirie, Australia. Anthropogenic Pb inputs are at their greatest from 1900 to 1910 and from 1960 to 1980. During the 20th century, Ba concentrations are consistently higher than ‘natural’ levels and are attributed to increased dust production, suggesting the influence of climate change and/or changes in land coverage with vegetation.